A compact model and direct parameters extraction techniques For amorphous gallium-indium-zinc-oxide thin film transistors. (December 2016) - Moldovan, Oana; Castro-Carranza, Alejandra; Cerdeira, Antonio; Estrada, Magali; Barquinha, Pedro; Martins, Rodrigo; Fortunato, Elvira; Miljakovic, Slobodan; Iñiguez, Benjamin
Highlights: We present a compact drain current model for the AOS TFTs, specifically GIZO TFTs. A direct parameters extraction technique is used. The output saturation behavior of the model is improved by a new asymptotic function. The model is compared with experimental measurements obtaining very good results. The model, in Verilog-A code, is implemented in EDA tools, such as Smart Spice. Abstract: An advanced compact and analytical drain current model for the amorphous gallium indium zinc oxide (GIZO) thin film transistors (TFTs) is proposed. Its output saturation behavior is improved by introducing a new asymptotic function. All model parameters were extracted using an adapted version of the Universal Method and Extraction Procedure (UMEM) applied for the first time for GIZO devices in a simple and direct form. We demonstrate the correct behavior of the model for negative VDS, a necessity for a complete compact model. In this way we prove the symmetry of source and drain electrodes and extend the range of applications to both signs of VDS . The model, in Verilog-A code, is implemented in Electronic Design Automation (EDA) tools, such as Smart Spice, and compared with measurements of TFTs. It describes accurately the experimental characteristics in the whole range of GIZO TFTs operation, making the model suitable for the design of circuits using these types of devices.